(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The last decade has been characterized by the rapid development of information technologies that are fundamentally changing society. Economic relations have become extremely dependent on infrastructural information support, social relations have shifted from the sphere of exclusively direct interaction to territorially and temporally distant due to the possibilities of digital space. Such radical transformations require a new approach to understanding the consequences of these processes, the ability to adapt digital technologies to the contemporary requirements of society and business. Therefore, the purpose of this article is to expose the content and features of implementing the concept of digital competencies, to identify the perspectives and benefits of developing a competency-based approach in an information society environment. Conduct a digital competence framework analysis and develop a digital competency framework for the human capital of business entities. The practical results are the developed framework of digital competencies for the human capital of business organizations. Reflecting the level of digital maturity of the company and the level of digital literacy of human capital. In the digital age, it is necessary to improve the quality and effectiveness of education aimed at preparing young people for life in the digital society, acquiring relevant digital skills, digital literacy for the population and business. The increasing need to use modern computer technology in the workplace has led to the need to increase computer literacy for most professions. The digital competencies of human capital are the basis for digital transformation of business.